1996
DOI: 10.1097/00007632-199601010-00026
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Spinal Canal Decompression in Burst Fractures Treated With Pedicle Screw Instrumentation

Abstract: Indirect decompression in burst fractures averages about half of the preexisting encroachment. Results are usually better at T12 and L1 than at L2. Additional or secondary decompression is rarely indicated if these fractures are treated early and by experienced surgeons. Burst Type B fractures in patients older versus younger than 40 years of age differ in many respects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 31 publications
0
36
0
2
Order By: Relevance
“…Conservative treatment still has its advocates and appears to yield acceptable results [17]. There is a trend towards short segment fixation either anteriorly or posteriorly [3,13,15,20], with results reported to be superior to those obtained by conservative management. However, a comparison of results may be unreliable due to different methods of assessment of outcome [12].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment still has its advocates and appears to yield acceptable results [17]. There is a trend towards short segment fixation either anteriorly or posteriorly [3,13,15,20], with results reported to be superior to those obtained by conservative management. However, a comparison of results may be unreliable due to different methods of assessment of outcome [12].…”
Section: Discussionmentioning
confidence: 99%
“…Hollowell et al [18] observed that preservation of the endplate did not significantly increase the resistance to graft subsidence and the titanium cage construct provided the greatest resistance to axial load. The effect of decompression of the vertebral canal on the recovery from neurological deficits continues to be a controversial subject, although clinical and experimental studies have suggested it has a beneficial effect in patients with incomplete neurological damage [13,26]. It is difficult to establish a threshold of canal compromise ratio above which surgical decompression is needed to prevent late neurological deficits in the thoracolumbar burst fracture [11,23].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with bony fragments invading medullary canal without neurological compromise, it is enough to achieve adequate stability. 37,39,40 Patients with kyphosis >358 need surgical stabilization due to the high risk of progressing to worse outcomes. [39][40][41][42] 8.3.…”
Section: Indicationsmentioning
confidence: 99%
“…37,39,40 Patients with kyphosis >358 need surgical stabilization due to the high risk of progressing to worse outcomes. [39][40][41][42] 8.3. Short, long segment instrumentation, or adding a screw to the fractured vertebrae Controversy still exists over how many segments should be fixed when treating a thoracolumbar fracture.…”
Section: Indicationsmentioning
confidence: 99%